The Effect of Mathematical Prior Knowledge and Problem-Based Learning on Students’ Problem-Solving Ability in Calculus - Claudia Betruchy Bada (PT. Integrasi Sains Edukasi, 2025)
Students with low initial mathematical understanding have difficulty solving mathematical problems especially in Calculus subject that require higher-order thinking skills, one of which is problem-solving ability. Then, problem-solving skills need to be developed using Problem Based Learning models. This study aims to examine the influence of mathematical prior knowledge (MPK) and the problem-based learning (PBL) model on the problem-solving ability of Computer Engineering students at UNIPA in calculus. This quantitative study uses a factorial experimental design. Data were collected through documentation and test instruments, and analyzed using factorial ANOVA with SPSS 23. The results show that students in the PBL class had significantly higher problem-solving ability compared to those in the control class. Furthermore, students with high MPK in the PBL group scored the highest. It can be concluded that both MPK and PBL significantly affect students’ problem-solving ability in calculus.